Antibiofilm Effects of Macrolide Loaded Microneedle Patches: Prospects in Healing Infected Wounds - Arshad, Muhammad Sohail; Zahra, Aleema Tehreem; Zafar, Saman; Zaman, Hussain; Akhtar, Ambreen; Ayaz, Muhammad Mazhar; Kucuk, Israfil; Maniruzzaman, Mohammed; Chang, Ming-Wei; Ahmad, Zeeshan (Pharmaceutical research, 2021)
Aim The aim of this study was to fabricate polymeric microneedles, loaded with macrolides (erythromycin, azithromycin), using hyaluronic acid and polyvinyl pyrollidone. Methods These microneedles were fabricated using a vacuum micromolding technique. The integrity of the microneedle patches was studied by recording their morphologic features, folding endurance, swelling and micro-piercing. Physicochemical characteristics were studied by differential scanning calorimetry, thermogravimetric analysis and fourier transform infrared spectroscopy. In-vitro drug release, antibiofilm and effect of microneedle patch on wound healing were also studied to confirm the efficacy of the formulations. Results Formulated patches displayed acceptable folding endurance (>100) and uniform distribution of microneedles (10 × 10) that can penetrate parafilm. Differential scanning calorimetry results depict a decrease in the crystallinity of macrolides following their incorporation in to a polymer matrix. Percentage release of azithromycin and erythromycin from the polymeric patch formulations (over 30 min) was 90% and 63% respectively. Broadly, the zone of bacterial growth inhibition follows the same order for Staphylococcus aureus , Escherichia coli and Salmonella enterica . After 5 days of treatment with azithromycin patches, the wound healing was complete and skin structure (e.g. hair follicles and dermis) was regenerated. Conclusion It was concluded that azithromycin loaded microneedle patches can be used to treat biofilms in the infected wounds. Graphical abstract